Electrode tissue coupling is a new main determinant of RF lesion creation, experience from a cardiac animal model. (19th May 2022) - Wachter, A; Bahlke, F; Popa, M; Foerschner, L; Krafft, H; Maurer, S; Englert, F; Telishevska, M; Lengauer, S; Kottmaier, M; Lennerz, C; Reents, T; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Radiofrequency (RF) current is a classic ablation technology used in the EP lab. By now it is assumed that RF lesion size is mainly determined by RF power, duration and contact force. This ex vivo animal model study shows that a new parameter - "electrode tissue coupling" (ETC) - plays an additional major role in RF lesion creation. The ETC level describes the amount of electric contact between the RF electrode and cardiac tissue: In minor ETC levels, only the distal electrode connects to tissue. In full ETC levels, the whole RF electrode is embedded in cardiac tissue. Methods: RF-lesions were created using an ex vivo porcine cardiac model. The experimental setup consisted of a saline-filled container, a dispersive electrode, a heated thermostat and a circulation pump to imitate in vivo conditions. Global impedance was kept at 120 Ohm as well as the temperature at 37°C. RF-lesions were created using identic values of RF duration and contact force. A RF power of 20W, 30W, 40W, and 50W was used. The ETC levels were systematically varied between minor and full coupling. All parameters (power, temperature, global and local impedance, contact force, ETC, lesion size) were measured constantly during application of RF-current, enabling real-time correlation of RF parameters and lesion size. Results: In total, 1923 measurements during application of RF-current were analyzed. In ETC III (full tissue coupling), lesions became significantly wider and deeper. In 20W ablations, lesion diameters were significantly (1.68 fold) larger when applying ETC III instead of ETC I. This relation was found in variations of RF parameters (Table 1). Interestingly, baseline local impedance and local impedance drop showed a high correlation with selected ETC levels. The average baseline local impedance in ETC I was 207.2 Ohm, compared to 267.3 Ohm in ETC III (p < 0.01). Discussion: In addition to by now known parameters (power, duration, contact force), electrode tissue coupling is a main determinant of lesion size. Higher ETC levels result in higher amounts of RF current going into adjacent tissue instead of current dissipation into the blood pool. In clinical practice, the ETC level can be predicted by baseline local and global impedance. Observation of these parameters should become clinical practice during RF ablation.